Effect of drying methods and extraction solvent on the total phenolic content and antioxidant activity of pulp and peel extracts of benincasa hispida - Noorashikin, Ab Wahab (2014)
Benincasa hispida (B. hispida) also known as kundur, a member of cucurbitacea (cucurbit) family that gain highly attention as their biological function such as antioxidant, antimutagenic activities and high in polyphenol content. The foods that we eat contain high chemical composition especially ready to eat food thus, it is important to know the basic nutrition content from the food. With increasing the variety of food production, the increasing in antioxidant activity needed in order to prevent serious health’s problem. Natural antioxidant usually comes from plant and from variety part of plants, it also contains its antioxidant value and phenolic content. The objective of this study is to evaluate how drying process of peel and pulp of B. hispida also by using different solvent can affect the antioxidant activity and total phenolic content (TPC) of the peel and pulp extracts. The effects of different drying proces (microwave dried and oven dried) and different solvent systems (ethanol, methanol, ethanol-water 80:20 and methanol-water 80:20) were assessed on the antioxidant activity and total phenolic contents of B. hispida peel and pulp. Antioxidant activities of the sample were determined through DPPH radical scavenging activity, while the TPC was determined spectrophotometrically using Folin-Ciocalteae assay. There was a difference in the extracting ability of each of the solvents. The aqueous solvents were superior in their ability to extract the antioxidants and aqueous methanol was significantly more efficient than aqueous ethanol as shown by the TPC results. As for DPPH, oven-dried pulp samples extracted by methanol solvent showed the highest scavenging activity at 96.55%. The pulp samples showed the highest radical scavenging activity of 81.98% (microwave-dried) and 97.80% (oven-dried) when extracted using 100% ethanol. Meanwhile the peel samples demonstrated highest radical scavenging activities at 68.35% (microwave-dried) and 81.84% (oven-dried) when extracted by aqueous methanol. The findings of this study revealed that 80% methanol and 100% ethanol are the best two extraction solvents used for obtaining the highest antioxidant activities Also, the peel and pulp samples drying process prior to extraction, also influenced the extraction yield. Oven dried peel samples had the highest yield while oven dried pulp had the lowest. From the result it shows that oven-dried has the best drying method by using aqueous methanol for antioxidant activity. While, for total phenolic content aqueous methanol show the best extraction solvent with microwave-dried. The result obtained demonstrated the potential of the peel and pulp of B. hispida as an alternative source of antioxidant agents